2000
DOI: 10.1002/1521-4095(200009)12:17<1286::aid-adma1286>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle-Directed Growth of Silica

Abstract: Silica‐coated vesicles have been produced by the deposition of silica onto unilamellar vesicles from aqueous solution for the first time. The quaternary ammonium surface of the surfactant vesicles is receptive to silica and facilitates deposition of up to 5–10 nm of it. The “petrified” vesicles are stable to dehydration and can be visualized by conventional TEM (see Figure) without additional staining agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
150
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(152 citation statements)
references
References 4 publications
1
150
1
Order By: Relevance
“…The first category is hollow particles characterized by pores that are distributed uniformly throughout their shells. Particles with this morphology are most often synthesized by using a large core template such as a nonpolar solvent, [8,9] microemulsion droplets, [10] pre-existing vesicles, [11][12][13][14] or latex microspheres. [15,16] Microporous or mesoporous silica coats the core template, and the template is removed to leave a hollow core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first category is hollow particles characterized by pores that are distributed uniformly throughout their shells. Particles with this morphology are most often synthesized by using a large core template such as a nonpolar solvent, [8,9] microemulsion droplets, [10] pre-existing vesicles, [11][12][13][14] or latex microspheres. [15,16] Microporous or mesoporous silica coats the core template, and the template is removed to leave a hollow core.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prepare vesicular structures using these surfactants, special treatments have to be used to generate the vesicles. [11,21] In contrast to hydrogenated surfactants, partially fluorinated surfactants are prone to form low-curvature structures such as discs, bilayers, and vesicles. [22] We first reported the formation of vesicular silica with mesoporous shells by using the partially fluorinated surfactant CF 3 (CF 2 ) 7 (CH 2 ) 2 PyCl as a template, although in that case the walls seem to be formed from packed micelles rather than bilayers of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, very large hollow spheres (a few micrometers in diameter) with mesoporous walls were obtained, in which high intrusion energy (high stir speed) was often involved [11]. In other works, vesicle structures [12], giant surfactant superstructures [13,14], even bubbles etc. have been used to assist in the construction of macro-mesoporous materials.…”
Section: Introductionmentioning
confidence: 58%
“…Our systematic study using different types of surfactant and different silica-precursors clearly has shown that successful deposition of silica on the vesicles is possible. [10] A silica deposit of about 10 nm can be achieved. These so-called ªpetrifiedº vesicles are stable to dehydration and can be visualized using conventional transmission electron microscopy (TEM) without additional staining (Fig.…”
Section: Vesicle-directed Growthmentioning
confidence: 99%